Discussing Socio-Scientific Issues on Twitter: The Quality of Pre-Service Science Teachers’ Arguments - Nurhan Ozturk; Esra Bozkurt-Altan; Ayse Yenilmez-Turkoglu (Journal of Education in Science, Environment and Health)
The purpose of this study is to determine pre-service science teachers’ (PSTs’) argument qualities in the process of discussing some SSIs on Twitter. In this respect, firstly, sources that PSTs use to reach information and ranking of these sources as they access information were taken. The study is designed as a case study and the participants were 13 PSTs (11 females, 2 males). Data were collected through arguments written on Twitter and after classroom discussions, and field notes taken by the researchers. The findings showed that PSTs use Internet, books and social media tools as they try to reach information and spend at least 1 to 5 hours in social media during the day. The findings also showed that online discussions on Twitter developed their argumentation qualities. This may indicate that as PSTs become familiar with writing arguments and realize that they need to consider the elements of arguments, they produce better arguments. It is therefore recommended to the researchers and teachers to provide students with environments where they can be active and conduct informal discussions about SSIs. Social media tools (Facebook, Instagram, YouTube, etc.), at this point, may provide with a useful option.